The role of financial literacy in shaping stock market investment behaviour of generation Z in Klang Valley / Nur Aqilah Zainordin ... [et al.] - Zainordin, Nur Aqilah; Ann, Anna Lee Shue; Kho, Yin Xuan; Mohd Rosli, Nor Aziyatul Izni; Annuar, Nursyamilah (Universiti Teknologi MARA, Perlis, 2025)
This study examined the factors influencing stock market investment decisions among Generation Z in Klang Valley based on herding behaviour, advocate recommendations, social media influence, and financial literacy. This study aims to provide valuable insights into the key drivers behind stock investment decisions among Generation Z, aiming to fill the knowledge gap, particularly in the Klang Valley region. The research integrates three theoretical frameworks to understand how these factors affect investment choices: the Theory of Planned Behavior, Behavioral Finance Theory, and Social Cognitive Theory. Data from 450 respondents aged 18-27 were collected via questionnaires using SPSS Version 29. The study adopted a quantitative, cross-sectional design and convenience sampling. The findings revealed that herding behaviour, social media influence, and financial literacy significantly and positively impact stock investment decisions, with financial literacy being the most influential. Conversely, advocate recommendations were found to have minimal and statistically insignificant impact on stock investment decisions. The study also outlined theoretical and practical implications, limitations, and suggestions for future research.